2023
DOI: 10.1101/2023.03.03.530753
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A unique symbiosome in an anaerobic single-celled eukaryote

Abstract: Symbiotic relationships drive evolutionary change and are important sources of novelty. Here we demonstrate a highly structured syntrophic symbiosis between species of the anaerobic protistAnaeramoeba(Anaeramoebae, Metamonada) and bacterial ectosymbionts. We dissected this symbiosis with long-read metagenomics, transcriptomics of host and symbiont cells coupled with fluorescent in situ hybridization (FISH), and microscopy. Genome sequencing, phylogenomic analyses and FISH show that the symbionts belong to theD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 75 publications
(120 reference statements)
0
12
1
Order By: Relevance
“…13A in Táborský et al, 2017). Notably, Jerlström-Hultqvist et al (2023) showed that the membrane of symbiont vesicles is not continuous, that is, the "pouches" are actually deep invaginations of the cell membrane and their interior is in contact with the outer environment, at least in A. flamelloides and A. ignava. They also identified the symbionts as sulfate-reducing Deltaproteobacteria, which explains the importance of the access of the symbionts to the outer environment and relatively high sulfate concentrations of marine water.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…13A in Táborský et al, 2017). Notably, Jerlström-Hultqvist et al (2023) showed that the membrane of symbiont vesicles is not continuous, that is, the "pouches" are actually deep invaginations of the cell membrane and their interior is in contact with the outer environment, at least in A. flamelloides and A. ignava. They also identified the symbionts as sulfate-reducing Deltaproteobacteria, which explains the importance of the access of the symbionts to the outer environment and relatively high sulfate concentrations of marine water.…”
Section: Discussionmentioning
confidence: 99%
“…The MROs form a cluster with symbiotic prokaryotes in the cytoplasm. It was shown only recently that the symbionts are sulfate-reducing Desulfobacter-related bacteria, which were acquired at least twice independently within the Anaeramoeba lineage (Jerlström-Hultqvist et al, 2023). Although they were originally considered endosymbionts by Táborský et al (2017), they likely reside within deep cell membrane invaginations and are exposed to the outer environment (Jerlström-Hultqvist et al, 2023).…”
Section: Anaeramoeba Pumila Sp Nov and Anaeramoeba Sp Oce22c Represen...mentioning
confidence: 99%
See 3 more Smart Citations